ERK inhibitor LY3214996-based treatment strategies for RAS-driven lung cancer - Köhler, Jens (Mol Cancer Ther, 2021)
RAS gene mutations are the most frequent oncogenic event in lung cancer. They activate multiple RAS-centric signaling networks among them the MAPK, PI3K and RB pathways. Within the MAPK pathway ERK1/2 proteins exert a bottleneck function for transmitting mitogenic signals and activating cytoplasmic and nuclear targets. In view of disappointing anti-tumor activity and toxicity of continuously applied MEK inhibitors in patients with KRAS mutant lung cancer, research has recently focused on ERK1/2 proteins as therapeutic targets and on ERK inhibitors for their ability to prevent bypass and feedback pathway activation. Here we show that intermittent application of the novel and selective ATP-competitive ERK1/2 inhibitor LY3214996 exerts single-agent activity in patient-derived xenograft (PDX) models of RAS mutant lung cancer. Combination treatments were well tolerated and resulted in synergistic (ERKi plus PI3K/mTORi LY3023414) and additive (ERKi plus CDK4/6i abemaciclib) tumor growth inhibition in PDX models. Future clinical trials are required to investigate if intermittent ERK inhibitor-based treatment schedules can overcome toxicities observed with continuous MEK inhibition and - equally important - to identify biomarkers for patient stratification.